Effects of carbohydrate supplementation on competitive runners undergoing overload training followed by a session of intermittent exercise - de Sousa, M. V.; Madsen, K.; Simoes, H. G.; Pereira, R. M. R.; Negrao, C. E.; Mendonca, R. Z.; Takayama, L.; Fukui, R.; da Silva, M. E. R. (European Journal of Applied Physiology, 2010)
This study evaluated the effects of a micro cycle of overload training (1st-8th day) on metabolic and hormonal responses in male runners with or without carbohydrate supplementation and investigated the cumulative effects of this period on a session of intermittent high-intensity running and maximum-performance-test (9th day). The participants were 24 male runners divided into two groups, receiving 61% of their energy intake as CHO (carbohydrate-group) and 54% in the control-group (CON). The testosterone was higher for the CHO than the CON group after the overload training (694.0 ± 54.6 vs. CON 610.8 ± 47.9 pmol/l). On the ninth day participants performed 10 × 800 m at mean 3 km velocity. An all-out 1000 m running was performed before and after the 10 × 800 m. Before, during, and after this protocol, the runners received solution containing CHO or the CON equivalent. The performance on 800 m series did not differ in either group between the first and last series of 800 m, but for the all-out 1000 m test the performance decrement was lower for CHO group (5.3 ± 1.0 vs. 10.6 ± 1.3%). The cortisol concentrations were lower in the CHO group in relation to CON group (22.4 ± 0.9 vs. 27.6 ± 1.4 pmol/l) and the IGF1/IGFBP3 ratio increased 12.7% in the CHO group. During recovery, blood glucose concentrations remained higher in the CHO group in comparison with the CON group. It was concluded that CHO supplementation possibly attenuated the suppression of the hypothalamic-pituitary-gonadal axis and resulted in less catabolic stress, and thus improved running performance.